2003
DOI: 10.1093/humrep/deg163
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer and Hodgkin's disease: evaluation of semen quality

Abstract: Better semen quality was observed in patients with HD than in those with TC. The semen quality observed in our TC and HD groups seems better than previous results reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 45 publications
9
38
1
2
Order By: Relevance
“…These data are in agreement with previous studies. 16,17 The lowest baseline sperm concentration was detected in the TNCT group, while the TNRT group showed higher baseline FSH levels when compared to the TNCT group, likely because of the presence of elevated b-hCG levels with FSH (and spermatogenesis) inhibition in some TNCT patients with non-seminomatous germ cell tumors. 18 On the other hand, baseline inhibin B levels were higher in LDCT and LDRT groups than in TNCT and TNRT groups.…”
Section: Discussionmentioning
confidence: 94%
“…These data are in agreement with previous studies. 16,17 The lowest baseline sperm concentration was detected in the TNCT group, while the TNRT group showed higher baseline FSH levels when compared to the TNCT group, likely because of the presence of elevated b-hCG levels with FSH (and spermatogenesis) inhibition in some TNCT patients with non-seminomatous germ cell tumors. 18 On the other hand, baseline inhibin B levels were higher in LDCT and LDRT groups than in TNCT and TNRT groups.…”
Section: Discussionmentioning
confidence: 94%
“…33 Given that patients with fever nearly always had night sweats as well, it was not possible to determine which of the individual B-symptoms had the strongest impact. Another limitation of our study is that only patients with early stage disease were enrolled: two other studies 30,34 previously showed that advanced-stage disease has a greater negative effect than early-stage disease on semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Чаще нарушения сперма-тогенеза наблюдаются при лимфоме Ходжкина (ЛХ), неходжкинской лимфоме (НХЛ), остром лимфобласт-ном лейкозе (ОЛЛ), опухолях яичка [9,10] и проявля-ются снижением показателей спермограммы [11][12][13]. По разным данным, инициальные нарушения сперма-тогенеза встречаются от 25 до 70 % при ЛХ и других опухолях [6,[14][15][16][17]. Неспецифическое влияние опухо-ли на сперматогенез происходит при длительном суб-фебрилитете, потере веса, значительной распростра-ненности опухолевого процесса или очага и других системных нарушениях [18][19][20].…”
Section: влияние опухолевого процесса на сперматогенезunclassified
“…Дмитрия Рогачева были направлены на криоконсервацию 30 человек, средний возраст кото-рых составил 16 (15)(16)(17) Работа над проблемой сохранения фертильности у юношей сопряжена с трудностями, которые условно можно разделить на несколько групп: связанные с информированием, клиническими, физиологиче-скими, юридическими, этическими и финансовыми ограничениями.…”
Section: (рис 2)unclassified